PENGARUH KOMPETENSI MANAJERIAL KEPALA PAUD TERHADAP KINERJA PENDIDIK DI PAUD NON FORMAL KABUPATEN SERANG - Mutoharoh, Mutoharoh; Hufad, Achmad; Rusdiyani, Isti (Universitas Tanjungpura, 2023)
The principal as a manager has an important role in managing resources within the educational unit. The performance of educators is an important factor in improving the quality of education. This study aims to determine whether there is an influence of managerial competence in improving the performance of educators in non-formal PAUD Serang Regency. The results showed a simple linear regression equation Y = a + bx, with a value of Y = 13.670 + 1.702X, which means the coefficient b is positive, this indicates that changes in educator performance (Y) are in line with changes in managerial competence (X). So the value of Y will increase if X increases, otherwise if X decreases then Y will decrease. The correlation coefficient value is 0.552 with the provision that the specified coefficient interval value can be concluded that the correlation between X and Y variables is strong. From the calculation of the coefficient of determination above, it is obtained from the value of 55.2% while the remaining 44.8% is influenced by other factors. The results of hypothesis testing showed that tcount value was greater than ttable, namely 19,325 t table 7,739, so H0 was rejected and Ha was accepted so that it can be concluded that there is a positive and significant influence on the managerial competence of the PAUD head and the performance of educators in non-formal PAUD Serang district.